2016
DOI: 10.5966/sctm.2016-0175
|View full text |Cite
|
Sign up to set email alerts
|

A Human Corneal Epithelial Cell Line Model for Limbal Stem Cell Biology and Limbal Immunobiology

Abstract: Limbal stem cell (LSC) deficiency is a visually debilitating condition caused by abnormal maintenance of LSCs. It is treated by transplantation of donor‐derived limbal epithelial cells (LECs), the success of which depends on the presence and quality of LSCs within the transplant. Understanding the immunobiological responses of these cells within the transplants could improve cell engraftment and survival. However, human corneal rings used as a source of LSCs are not always readily available for research purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…The images were processed using Zen (blue edition) software from Carl Zeiss. In additional experiments, the ABCB5 antibody was validated against previously established ABCB5 monoclonal (clone 5H3C6) (data not shown).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The images were processed using Zen (blue edition) software from Carl Zeiss. In additional experiments, the ABCB5 antibody was validated against previously established ABCB5 monoclonal (clone 5H3C6) (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, the ATP binding cassette subfamily B member 5 (ABCB5) surface protein, has been suggested as a putative hLESCs marker. Recent findings have shown that ABCB5 is critical for corneal epithelial homeostasis and repair and it is often co‐expressed with p63 in hLESCs both in situ and ex situ . However, many concerns were recently raised regarding the ability of p63, as well as of ABCB5 to accurately detect hLESCs .…”
Section: Introductionmentioning
confidence: 99%
“…A small amount of LSCs are hidden among the LECs, which account for only 0.5–10% [ 18 ], resulting in the difficulties with isolating the LSCs with such low frequency from such complex limbal epithelium suspension. As reported, there were some traditional methods to isolate the LSCs such as gradient centrifugation [ 120 ], FACS [ 121 ], and magnetic-activated cell sorting (MACS) [ 64 ]. All of these methods are based on enzyme digestion, which potentially changes gene expression patterns and protein profiles of LSCs, and increases the risk of contamination of suspension due to complicated operations [ 122 , 123 , 124 ].…”
Section: Difficulties In the Study Of Lsc-specific Biomarkersmentioning
confidence: 99%
“…This discovery identified ABCB5 as the first molecular surface marker for prospective LSC enrichment by antibody-based cell sorting. Furthermore, Abcb5 gene loss of function in Abcb5 -knockout mice was associated with defective corneal differentiation and regeneration, indicating that ABCB5, beyond representing an LSC marker [ 24 27 ], is required for LSC function and corneal epithelial regeneration [ 23 ]. Purified CK12 − ABCB5 + LSCs could, in vitro, be induced to differentiate into CK12 + epithelial cells [ 28 ].…”
Section: Introductionmentioning
confidence: 99%